C-scorpionate iron(II) complexes as highly selective catalysts for the hydrocarboxylation of cyclohexane - Matias, Inês (2019)
The C-scorpionate iron(II) complexes [FeCl2{kappa(3)-HC(pz)(3)}](1) (pz = pyrazol-1-yl), Li[FeCl2{kappa(3)-SO3C(pz)(3)}] (2) and the new [FeCl2{kappa(3)-HOCH2C(pz)(3)}] (3) act as catalysts for the hydrocarboxylation of cyclohexane (with CO and H2O) to cyclohexanecarboxylic acid in a remarkable yield (up to 60%) and under mild conditions. The catalysts selectivity for the acid can be tuned by CO pressure, catalyst amount and reaction temperature. Complex [FeCl2{kappa(3)-HC(pz)(3)}] (1) provides the most effective catalyst requiring low CO pressure. This work constitutes an unprecedented use of iron complexes as catalysts for the hydrocarboxylation of alkanes.